Biocatalytic Synthesis of α-Amino Ketones - Chun, Stephanie W.; Narayan, Alison R. H. (Synlett, 2019)
Stereospecific generation of α-amino ketones from common α-amino acids is difficult to achieve, often employing superstoichiometric alkylating reagents and requiring multiple protecting group manipulations. In contrast, the α-oxoamine synthase protein family performs this transformation stereospecifically in a single step without the need for protecting groups. Herein, we detail the characterization of the 8-amino-7-oxononanoate synthase (AONS) domain of the four-domain polyketide-like synthase SxtA, which natively mediates the formation of the ethyl ketone derivative of arginine. The function of each of the four domains is elucidated, leading to a revised proposal for the initiation of saxitoxin biosynthesis, a potent neurotoxin. We also demonstrate the synthetic potential of SxtA AONS, which is applied to the synthesis of a panel of novel α-amino ketones.1 Introduction2 Native SxtA Module Activity3 New Reactions with SxtA AONS4 Conclusions and Outlook
Keywords: biocatalysis; biosynthesis; α-oxoamine synthases; neurotoxins; α-amino ketones; pyridoxal-5′-phosphate